Identifying crop diseases using attention embedded MobileNet-V2 model - Chen, Junde; Zhang, Defu; Suzauddola, Md; Zeb, Adnan (Applied soft computing, 2021)
Various crop diseases are a major problem worldwide since their occurrence leads to a significant decrease in crop production. The image-based automatic identification of crop diseases that involves food security has attracted much attention recently. It is a challenging research topic due to the complexity of crop disease images, such as clutter field backdrops and irregular lighting strengths. A variety of deep learning networks, especially CNNs, are becoming the mainstream methods for addressing many challenges correlated with image recognition and classification. In this study, to improve the learning ability of minor lesion features, we introduced the Location-wise Soft Attention mechanism to the pre-trained MobileNet-V2, in which the general knowledge of images learned from ImageNet was migrated to our crop disease recognition mode, namely, CDRM. Further, a localization strategy was embedded in the proposed network, and the two-phase progressive strategy was executed for model training. The proposed method shows substantial efficacy in the experimental analyses. It reached a 99.71% average accuracy on the open-source dataset, and even under cluttered background conditions, the average accuracy attained 99.13% for the identification of crop diseases. Experimental findings deliver a competitive performance compared to other state-of-the-art methods and also indicate the efficacy and extension of the proposed method. Our code is available at https://github.com/xtu502/crop-disease-recognition-model. •Embed MobileNet V2 with Location-wise Soft Attention to extract tiny lesion features.•Visualization technology of plant disease activation map was embedded in the network.•Transfer learning and two-stage progressive strategy were executed in model training.•Compare this review with existing state-of-the-art methods.